Metastatic Renal Cell Carcinoma Presenting as Gastric Ulcer: Case Report and Literature Review - Alhareth Al Juboori; Satinder Kaur; Atigadda Reddy (Case Reports in Gastrointestinal Medicine)
Renal cell carcinoma (RCC) accounts for approximately 3% of all adult malignancies. True gastrointestinal metastases, specifically to gastric wall, have been rarely observed. Herein we describe a case of delayed metastasis to gastric wall occurring more than a decade after previously curative nephrectomy for RCC. A 67-year-old male with history of right radical nephrectomy in 2001 for RCC was found to have an asymptomatic right lower lobe solitary lung mass upon routine follow-up in 2011, with final biopsy results showing metastatic RCC for which he was treated accordingly. In 2014, patient was evaluated for dyspepsia with microcytic anemia and underwent an esophagogastroduodenoscopy and colonoscopy. EGD revealed a solitary one-centimeter atypical ulcer in the posterior mid gastric body with biopsy results being consistent with metastatic RCC. Our literature review has yielded thirty-six reported cases of RCC in association with gastric wall metastases.